2022
DOI: 10.1108/ilt-05-2021-0161
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and temperature-sensitive lubrication behavior of PNIPAM microgels for titanium alloy

Abstract: Purpose This paper aims to offeri novel nano-additives polymer microgels to precisely improve the lubrication properties of titanium alloy under different temperatures. Design/methodology/approach The surfactant-free emulsion polymerization method was used to prepare Poly(N-isoprolylacrylamide) (PNIPAM) microgels. A ball-on-disk tribometer was applied to investigated the temperature-sensitive lubrication behavior of PNIPAM microgels. Findings The results show that the as-prepared microgels are ball-like na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…From the TEM images in Figure 2, it could be seen that both PNIPAM and GQDs@PNIPAM microgels had similar spherical structures with uniform particle size distribution and good dispersion. The particle size of PNIPAM microgels was about 90 nm, which was reported in our previous work, 41 while the particle size of GQDs@PNIPAM microgels was about 70 nm. It showed that GQDs participated in the reaction during the preparation of GQDs@PNIPAM microgels, and affected the polymerisation of the long chains of the microgels, resulting in the smaller particle size of GQDs@PNIPAM microgels.…”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…From the TEM images in Figure 2, it could be seen that both PNIPAM and GQDs@PNIPAM microgels had similar spherical structures with uniform particle size distribution and good dispersion. The particle size of PNIPAM microgels was about 90 nm, which was reported in our previous work, 41 while the particle size of GQDs@PNIPAM microgels was about 70 nm. It showed that GQDs participated in the reaction during the preparation of GQDs@PNIPAM microgels, and affected the polymerisation of the long chains of the microgels, resulting in the smaller particle size of GQDs@PNIPAM microgels.…”
Section: Methodssupporting
confidence: 82%
“…Although many investigations about the lubrication roles of both PNIPAM and GQDs have been reported, 40,41 there are no reports on the synergistic lubrication performance of PNIPAM and GQDs nanocomposites. In particularly, to the authors' best knowledge, there is no work on the lubrication of GQDs@ PNIPAM microgels for titanium alloy machining process.…”
Section: Introductionmentioning
confidence: 99%
“…Such bio-hydrogels can modulate and regulate feedback control of drug release. As a temperature-responsive polymer, Poly(N-isopropylacrylamide) (PNIPAM) has lower critical solution temperatures (LCST) that are extremely close to the human physiological temperature, about 32 • C [14,15]. When the ambient temperature is higher than the LCST, hydrogen bonds are formed between the isopropyl amide groups on the molecular chain of PNIPAM and the polymer contracts, releasing the drug and water for targeted release, which improves the drug utilization rate [16].…”
Section: Introductionmentioning
confidence: 99%